2013
DOI: 10.1136/jnnp-2012-304102
|View full text |Cite
|
Sign up to set email alerts
|

Long-term subthalamic nucleus stimulation improves sensorimotor integration and proprioception

Abstract: Chronic STN DBS in PD normalises sensorimotor integration and proprioception, likely through long-term plastic changes in the basal ganglia thalamocortical circuit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 39 publications
3
22
0
Order By: Relevance
“…Preliminary data showing that sensorimotor cortex plasticity improves only after long-term synergistic combination of DBS with reduced doses of levodopa, but not after DBS alone (141). That long-term stimulation is required for restoring sensory afferent inhibition of M1(142) indicates that cerebellar control of sensory processing may also normalize only after chronic stimulation of STN.Does selective DBS of the ventral GPi but not of the dorsal GPi or STN simultaneously inhibit the propagation of pro-dyskinetic signals through both cortico-striatal synapses and cerebello-striatal synapses (relayed through CM/PF thalamic nuclei) on D1-bearing MSNs? It is already known that GPi has functional somatotopy (143) and that ventral GPi stimulation has anti-dyskinetic effects while dorsal GPi stimulation improves akinesia and induces dyskinesias (144).…”
Section: Proposed Model Of Parkinsonism and Levodopa-induced Dyskinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary data showing that sensorimotor cortex plasticity improves only after long-term synergistic combination of DBS with reduced doses of levodopa, but not after DBS alone (141). That long-term stimulation is required for restoring sensory afferent inhibition of M1(142) indicates that cerebellar control of sensory processing may also normalize only after chronic stimulation of STN.Does selective DBS of the ventral GPi but not of the dorsal GPi or STN simultaneously inhibit the propagation of pro-dyskinetic signals through both cortico-striatal synapses and cerebello-striatal synapses (relayed through CM/PF thalamic nuclei) on D1-bearing MSNs? It is already known that GPi has functional somatotopy (143) and that ventral GPi stimulation has anti-dyskinetic effects while dorsal GPi stimulation improves akinesia and induces dyskinesias (144).…”
Section: Proposed Model Of Parkinsonism and Levodopa-induced Dyskinesmentioning
confidence: 99%
“…Preliminary data showing that sensorimotor cortex plasticity improves only after long-term synergistic combination of DBS with reduced doses of levodopa, but not after DBS alone (141). That long-term stimulation is required for restoring sensory afferent inhibition of M1(142) indicates that cerebellar control of sensory processing may also normalize only after chronic stimulation of STN.…”
Section: Proposed Model Of Parkinsonism and Levodopa-induced Dyskinesmentioning
confidence: 99%
“…[64] In a subsequent longitudinal study these modulatory effects of STN DBS were demonstrated only at six months and not at one month, these findings suggested chronic stimulation is important in elicitation and potentially maintenance of physiological changes. [ • 65]…”
Section: Tms In Parkinson’s Diseasementioning
confidence: 99%
“…On the other hand, LAI is 524 reduced in PD and is unaffected by medications (Sailer et al, 525 2003). SAI and LAI normalized with STN-DBS in PD patients (Sailer 526 et al, 2007;Wagle Shukla et al, 2013). Thus, the effects of STN-527 DBS are not always the same as dopaminergic mediations as 528 dopaminergic medications reduced SAI, which was normalized by 529 DBS (Sailer et al, 2002).…”
mentioning
confidence: 91%